Low ICU Burnout in a Safety Net Hospital - LeClaire, Michele M. (Crit Care Explor, 2019)
Burnout tends to be high in ICU settings. Stressors include serious patient illness, round-the-clock acute events, and end-of-life (nonbeneficial) care. We report on an ICU with very low burnout scores. We sought to understand factors that might be responsible for these favorable outcomes. DESIGN: We compared ICU scores on burnout and its predictors with scores in non-ICU providers, merging scores in four ICUs (burn, medical, surgical, and pediatrics). Analyses included descriptive statistics, as well as general estimating equations to assess odds of burnout in ICU clinicians versus non-ICU clinicians. SETTING: Annual wellness survey performed in October 2017 at Hennepin Healthcare System, an integrated system of care that includes an urban safety net hospital in Minneapolis, MN. SUBJECTS: Six-hundred seventy-nine providers (physicians and advanced practice providers). INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Annual surveys are performed using the validated Mini-Z 10 item wellness instrument. The Mini-Z assesses stress, satisfaction, and burnout, as well as known predictors including work control, chaos, teamwork, values alignment, and electronic medical record-related stress. Response rate in ICUs was 70% (64% elsewhere). Ten percentage of ICU clinicians reported burnout versus 37% of other providers (p = 0.015). ICUs were characterized as having lower chaos, less stress, and very high teamwork and values alignment between clinicians and leaders. Odds of burnout were four times lower in ICU clinicians (odds ratio, 0.24; 95% CI, 0.06–0.96; p = 0.043). Of all Hennepin Healthcare System providers, those with values not aligned with leaders had 3.28 times the odds of burnout (95% CI, 1.92–5.59; p < 0.001). CONCLUSIONS: Low burnout can be present in a busy, safety net ICU. Explicitly aligning values between clinicians and leaders may hold promise as a remediable worklife factor for producing these favorable results.